Distinct Roles of Additives in the Improved Sensitivity to CO of Ag- and Pd-Modified Nanosized LaFeO3 - Valentina Chumakova; Artem Marikutsa; Vadim Platonov; Nikolay Khmelevsky; Marina Rumyantseva (Chemosensors, 2023)
Perovskite-type mixed-metal oxides are of particular interest as semiconductor gas sensors due to the variability in the material composition and the stability of sensing parameters. LaFeO3 is a p-type semiconductor with relatively high conductivity and gas sensitivity. However, less is known about the sensitivity and sensing mechanisms of LaFeO3 modified by catalytic noble metals. In this work, we used a microwave-assisted sol–gel method to synthesize perovskite LaFeO3 nanoparticles with an average size of 20–30 nm and a specific surface area of 6–8 m2/g. LaFeO3 was modified by 2–5 wt.% Ag and Pd nanoparticles via the impregnation route. Using X-ray photoelectron spectroscopy, the additives were observed in the partially oxidized states Ag2O/Ag and PdO/Pd, respectively. Electric conduction and sensitivity to noxious gases were characterized by electrophysical measurements. It was shown that LaFeO3 modified by Ag and Pd had improved sensitivity and selectivity to CO, and the sensing behavior persisted in a wide range of relative humidity. Pristine and Ag-modified LaFeO3 had the maximum sensitivity to CO at a temperature of 200 °C, while modification with Pd resulted in a decreased optimal operating temperature of 150 °C. In situ infrared spectroscopy revealed that supported Pd nanoparticles specifically catalyzed CO oxidation at the surface of LaFeO3 at room temperature, which was the likely reason for the improved sensitivity and decreased optimal operating temperature of LaFeO3/Pd sensors. On the other hand, Ag nanoparticles were deduced to activate CO oxidation by lattice oxygen at the surface of LaFeO3, providing enhanced CO sensitivity at a higher temperature.